Evaluation of Some Sugar Beet Genotypes Under Drought Stress Based on Selection Indices - Salah A. Okasha; Mohamed H. Mubarak (Journal of Agronomy Research, 2018)
This study was conducted to determine drought tolerant indices of some sugar beet genotypes under water stress and non-stress conditions. Nine sugar beet (Beta Vulgaris L.) genotypes were tested in a Split-plot experiment based on a randomized complete block design in three replications under three levels of water stress 100%, 75% and 50% from plant requirements at the experimental farm Faculty of Agriculture, Suez Canal University, Ismailia, Egypt during 2015/ 2016 and 2016 / 2017 seasons. Twelve drought tolerance indices were used in this study, stress sensitivity index (SSI), stress tolerance (TOL), mean productivity (MP), geometric mean (GMP), harmonic mean (HM),yield stability index (YSI), yield index (YI), stress tolerance index (STI), sensitivity drought index (SDI), relative drought index (RDI), drought response index (DI) and stress susceptibility percentage index (SSPI). GMP, MP and STI were more informative towards classification of better or superior genotypes with respect to tolerant and sensitive groups. The results showed that the genotypes with high STI, GMP and MP values were suitable for cultivation under drought stress and non-stress environments. Both Yp and Ys of root yield in the control-50% analysis had significantly positive correlated (P value<0.05) with MP, GMP, YI, HM and DI, This indicates that these indices were more effective in identifying high yielding genotypes under drought stress as well as non-stress conditions.Principal components analysis showed that the first two components in the control-50% analysis, genotype Bts 1237 and Temar were identified as the most stable high yielding genotypes in both environments
Keywords: Sugar beet- Tolerant indices